Efektivitas Pembelajaran Online Dengan Microsoft Teams Pada Pelajaran Matematika Materi Program Linear - Mu'ti, Yafita Arfina (LP. Ma'arif Janggan Magetan, 2020)
Abstract: This study aimed to discover the effectiveness of learning mathematics online using Microsoft Office 365 in Linear Program. This research is pre-experiment with One Group Pretest –Postest Design. The populations iof this research were all of slass XI students at SMA N 1 Geger. The experiment unit of this research was class XI consisted of 10 classes. The sample of this research was class XI Science 6. The data of the research were collected by using instruments which covered: 1) The students’ Mathematics learning test, 2) the students’ activity observation sheet, 3) learning implementation observation sheet, and 4) the students’ response questionnaire. The results of the research reveal that Mathematics learning online using Microsoft Office 365 on Linear Program is effective to improve learning result of class XI students at SMAN 1 Geger, proved by: 1) The average of Mathematics learning result of class XI students at SMAN 1 Geger is greter than 70, 2) The questionnaire obtained students positive response about the CTL learning, with 84% of the responses categorized as good, 3) The observation student activity obtained students tend to be more active.